Violence and discrimination against nursing students in a Colombian public university - Carmen Leonor Moreno-Cubillos; Luz Elena Sepúlveda-Gallego (Investigación y Educación en Enfermería, 2013)
Objective. To measure the frequency of acts of gender discrimination and violence against nursing students in a Colombian public university. Methodology. A cross-sectional descriptive study with a representative sample of 81 students in the nursing program was conducted during the first half of 2011. The information was taken through a self-filled survey, inquiring about the history of violence and discrimination during college life, taken place on campus and at practice sites. Results. Seventy percent of the students were subjected to one of 17 types of violent or discriminatory acts investigated during their university life in the university facilities or in practice sites. The most frequent events reported by students were: abuse of authority (43%), taunts, gestures and obscene compliments (32%), psychological aggression (27%); verbal aggression (19%); and discrimination due to physical appearance (12%). Conclusion. A high proportion of nursing students participating in the study were subjected to acts of violence and discrimination. It is necessary for the university to generate welfare strategies to change attitudes related to these actions.